2013
DOI: 10.4209/aaqr.2012.08.0211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treatment with a Natural Extract of Mukdenia Rossii (Oliv) Koidz and Unipolar Ion Emission on the Antibacterial Performance of Air Filters

Abstract: Airborne microorganisms are deposited on air filters when these are used to reduce aerosol concentrations in indoor environments. These microorganisms cause various undesirable effects, such as production of unpleasant odors and resuspension of bacterial and fungal spore bioaerosols into the indoor air. To resolve these issues, we investigated the antimicrobial effects of a natural extract of Mukdenia rossii (Oliv) Koidz and unipolar ion emission against bioaerosols deposited on air filters. The experimental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…4 shows SEM images of filter #56 and filter #90 with GSE and propolis deposited for film attachment tests. The liquid phases of GSE and propolis were coated on to the filters and then dried on the surfaces, producing different shapes compared to other studies in which natural products were deposited on the filters in the form of already dried isolated particles (Jung et al, 2011b;Lee et al, 2013). As seen from Fig.…”
Section: Film Attachment Methods On Antimicrobial Filtersmentioning
confidence: 91%
See 1 more Smart Citation
“…4 shows SEM images of filter #56 and filter #90 with GSE and propolis deposited for film attachment tests. The liquid phases of GSE and propolis were coated on to the filters and then dried on the surfaces, producing different shapes compared to other studies in which natural products were deposited on the filters in the form of already dried isolated particles (Jung et al, 2011b;Lee et al, 2013). As seen from Fig.…”
Section: Film Attachment Methods On Antimicrobial Filtersmentioning
confidence: 91%
“…Jung et al (2011b) investigated a natural plant extract from Sophora flavescens for application to antimicrobial air filters and reported that the prepared natural product on an antimicrobial filter was effective for inactivating Gram-positive bacteria such as Staphylococcus epidermidis and Bacillus subtilis. Lee et al (2013) investigated the antimicrobial effects of a natural extract of Mukdenia rossii and unipolar ion emission on air filters for use against S. epidermidis and noted that the inactivation rate was about 70% using natural extract-treated filters and was enhanced by a further 20% due to unipolar ion emission.…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli (Korean Collection for Type Cultures, KCTC 1039, Biological Resource Center, Korea) and Staphylococcus epidermidis (KCTC 1917) were selected as antimicrobial test bacteria. E. coli, a Gram-negative bacterium, is commonly used in bioaerosol research with S. epidermidis, which is Gram-positive [37][38][39]. The bacteria cultures of E. coli and S. epidermidis were incubated in a nutrient broth medium (beef extract 0.3% and peptone 0.5%; Becton Dickinson, Franklin Lakes, NJ, USA) at 37 • C for 24 h. Stationary-phase organisms were harvested by centrifugation (5000× g, 10 min) and washed three times with sterile distilled water.…”
Section: Preparation Of Tested Bacterial Bioaerosolsmentioning
confidence: 99%
“…NAIs were of use to remove airborne particles [19][20]. Charging particles by emitted ions and electromigration was established as the removal mechanism supported by NAIs [21][22]. Interaction between charged particles and the electric field produced by electrical discharge increased the migration velocity towards the indoor surfaces, finally aerosols were deposited on various surfaces, such as wall surfaces [21][22][23].…”
Section: Introductionmentioning
confidence: 99%